Implementation of Problem Based Learning Integrated TPACK to Promote Students’ Mathematical Reasoning Ability - Aprisal, Aprisal; Supriadi, Supriadi; Anaguna, Nursyam (Universitas Sulawesi Barat, 2024)
This Classroom-Action Research aimed to improve students’ mathematical reasoning ability as integrated with TPACK. In this research, TPACK was implemented by examining teachers’ ability in designing Microsite during the teaching and learning process. The subjects of this research were students in the eleventh grade, XI IPA 1, SMAN 1 Sarjo, Pasangkayu. 2 cycles were conducted as the research steps, such as making plans, conducting the actions, conducting observations, and conducting several reflections. The instruments used in this research were the PBL-TPACK learning implementation sheet and mathematical reasoning ability test. The results of the study revealed that at the end of cycle 2, the average score of teachers and students’ activities was in the very good category with total scores of 89.67% and 88.02% respectively. Meanwhile, the average score of students' mathematical reasoning ability was 90, with the maximum total number of all students. Based on the results of the study, it can be concluded that students' mathematical reasoning ability increased through the implementation of integrated PBl TPACK.